Strictly speaking, are they not Corporate Reorganizations? The Negative / Neutral Equity Blocks and the RTF No. 10923-8-2011: Some considerations and proposals for change - Tarazona Ospina, Gustavo Enrique (2014)
In the last years, the Peruvian Tax Court has been considered that a corporate spin off where a company transfers a “neutral” or “negative” equity block does not qualifies as a real spin off, hence it should apply the tax rules as if this operation was a common sale. The author analyzes this criterion, and concludes that spin off where a company transfers a “neutral” or “negative” equity block, constitutes a real spin off. As a consequence, it must apply the special tax rules established for the corporate spin off.